Облікове забезпечення та оподаткування туристичних послуг - Чернецька, Ольга Віталіївна; Chernetska, Olga; Губарик, Ольга Миколаївна; Gubarik, Olga; Саванчук, Тетяна Миколаївна; Savanchuk, Tetyana (Класичний приватний університет, 2020)
В статті проаналізовано особливості облікового забезпечення процесу надання туристичних послуг і систем оподаткування суб’єктів туристичного бізнесу в залежності від їх форм власності та видів посередницьких схем. Виділено суб'єкти туристичного бізнесу та види договорів в туристичному бізнесі. Акцентовано увагу на специфічному характері обліку операцій з відображення доходу, зумовленого організацією відносин між суб’єктами туристичного бізнесу. Наведено аспекти документального оформлення надання туристичних послуг для визначення доходів суб'єктів туристичного бізнесу та визначено особливості їх облікового забезпечення. Проаналізовано системи оподаткування господарських операцій з надання туристичних послуг та узагальнено варіанти податкового навантаження суб’єктів туристичного бізнесу. There were analyzed the features of accounting support for the process of providing tourist services and taxation systems of tourism businesses, depending on their forms of ownership and types of intermediary schemes. The specific of the tourism industry is the close cooperation with non-residents, although it necessitates compliance with the requirements of national accounting standards and Ukraine Tax Code. Domestic travel agents should optimize accounting procedures in order to reasonably and promptly reflect operations results and the accurate taxation process for the formation of high-quality financial reporting. Tourism business entities can be enterprises, institutions, organizations of any ownership forms, as well as individuals - entrepreneurs registered in the manner prescribed by law and licensed to provide tourism services. The article highlights the entities of the tourism business. Travel agents are engaged in of intermediary commercial activities for tour operators’ interests. The types of contracts for the tourism business were identified. The provision of travel services begins with contract and is the basis for the document flow of the tourism entities activities. Tour operators recognize income and expenses for each travel service contract. Attention was focused on the specifics of income accounting, due to the organization of relations between tourism entities. The aspects of documenting tourist services for determining income are described and the features of their accounting support were identified. Tourism business entities are payers of the relevant taxes. Tour operators and travel agents have the right to choose one of the taxation systems. The taxation systems were analyzed and the options for the tax burden for tourism enterprises were generalized. It is important to take into account all special aspects of activities in accordance with the tax legislation requirements to optimize tax burden and make management decisions to choose a tax system. This affects the financial and economic indicators of all tourism business entities.
Accounting support and taxation of tourist services
Keywords: туристичні послуги; tourist services; суб'єкти туристичного бізнесу; tourism business entities; документальне оформлення; documentation; облікове забезпечення; accounting; оподаткування; taxation